A new difluoromethoxyl-containing acrylate monomer for PEG-b-PDFMOEA amphiphilic diblock copolymers. Issue 40 (24th September 2018) - Liu, Haoyu; Lu, Guolin; Feng, Chun; Huang, Xiaoyu
Abstract : This article reports the first synthesis of a well-defined difluoromethoxyl-containing polyacrylate via ATRP. Abstract : A new monomer, 2-(difluoromethoxy)ethyl acrylate (DFMOEA), was first synthesized from commercially available 2-hydroxyethyl acrylate via a one-step difluoromethylation reaction. A series of well-defined poly(2-(difluoromethoxy)ethyl acrylate) (PDFMOEA) homopolymers were prepared via atom transfer radical polymerization (ATRP) of DFMOEA initiated by 2-bromopropionate. The M n of the obtained polymer increased linearly with the monomer conversion, and the dispersities were low throughout the polymerization ( M w / M n < 1.20) though some bimolecular recombination and side reactions occurred during the polymerization. The glass transition temperature ( T g ) of the homopolymers obtained by using differential scanning calorimeter (DSC) is about −44 °C, 9 °C higher than that of poly(2-methoxyethyl acrylate) (PMOEA) homopolymer, which indicated that the introduction of difluoromethoxyl is beneficial for increasing the T g . ATRP of DFMOEA initiated by a PEG-based macroinitiator provided poly(ethylene glycol)- b -poly(2-(difluoromethoxy)ethyl acrylate) (PEG- b -PDFMOEA) amphiphilic diblock copolymers with low dispersities ( M w / M n < 1.26). The critical micelle concentrations ( cmc ) of PEG- b -PDFMOEA amphiphilic diblock copolymers in aqueous solution were determined by fluorescence probe technique and the cmc values decrease gradually with the increase of the length of hydrophobic PDFMOEA segment. It was found that PEG- b -PDFMOEA amphiphilic block copolymers could self-assemble into spherical micelles with a diameter of around ca . 45 nm in aqueous media which were visualized by transmission electron microscopy (TEM).